Analysis of Factors Affecting Timeliness of Financial Reporting in Manufacturing Companies - Elsye Fatmawati; Siti Rohimah (Kusuma Negara Business School, 2022)
This study aims to find empirical evidence about the factors that affect the timeliness of financial reporting of manufacturing companies listed on the Indonesia Stock Exchange. The factors tested in this study are debt to equity ratio, profitability, ownership structure, auditor quality, and auditor turnover. The sample of this study uses 100 manufacturing companies that are consistently listed on the Indonesia Stock Exchange for the 2015-2017 period which were taken using the purposive sampling method. These factors were then tested using logistic regression at a significance level of 5 percent. The results of the study identify that profitability and ownership structure significantly affect the timeliness of the company's financial reporting, while the Debt to Equity Ratio, auditor quality, and auditor turnover have no effect on the timeliness of financial reporting of manufacturing companies listed on the Indonesia Stock Exchange.